The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5430/ijhe.v5n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Test Enhanced Learning: Swedish Teacher Students’ Perception of Quizzing

Abstract: Given previous findings on test enhanced learning, the present study examined the implementation of this practice in terms of quizzing, during the progress of a course. After completing the university course, 88 Swedish teacher students were asked to answer an adapted Retrieval Practice and Test Anxiety Survey. The results showed that students perceived quizzing to improve learning, and reduce test anxiety. Nonetheless, based on students' misconceptions regarding why quizzing actually enhances learning, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Another laboratory study also found that learning situations including a short test (on mathematical concepts and materials) were evaluated as more negative and as more stress-and anxietyinducing than learning situations including a reading control task (these findings were also independent of participants' trait stress or trait anxiety; Wenzel and Reinhard, 2021). Interestingly, contrary results were also found (see, e.g., Agarwal et al, 2014;Nyroos et al, 2016) and even though these can be explained due to methodological differences, replications are still advantageous. Apart from that, it is furthermore possible that these effects of tests on stress perceptions do not arise for learners with higher intelligence and that intelligence might moderate these negative effects.…”
Section: Tests and Perceptions Of Stress Or Anxietymentioning
confidence: 96%
See 1 more Smart Citation
“…Another laboratory study also found that learning situations including a short test (on mathematical concepts and materials) were evaluated as more negative and as more stress-and anxietyinducing than learning situations including a reading control task (these findings were also independent of participants' trait stress or trait anxiety; Wenzel and Reinhard, 2021). Interestingly, contrary results were also found (see, e.g., Agarwal et al, 2014;Nyroos et al, 2016) and even though these can be explained due to methodological differences, replications are still advantageous. Apart from that, it is furthermore possible that these effects of tests on stress perceptions do not arise for learners with higher intelligence and that intelligence might moderate these negative effects.…”
Section: Tests and Perceptions Of Stress Or Anxietymentioning
confidence: 96%
“…To further ensure that the test task would be without stakes or artificial stressors, we avoided using learning materials that might be stress-or anxiety inducing in themselves (like mathematical or statistical information; see, e.g., Wenzel and Reinhard, 2021 ) and applied a test in which participant did not even have to say their answers out loud in front of their peers (contrary to Wenzel and Reinhard, 2021 ; see also England et al, 2017 ). To adequately assess participants stress perceptions caused by the learning situation, we measured their state stress directly after they completed the respective learning task and explicitly instructed them to refer to their perceptions and experiences while learning (contrary to previous work where stress was assessed, for instance, before participants worked on the respective tests, after the tests but with a longer delay, or even retrospectively at the end of the academic year; see, e.g., Agarwal et al, 2014 ; Hinze and Rapp, 2014 ; Nyroos et al, 2016 ). Finally, we must note that our work was planned and conducted shortly before the onset of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%